Pseudocontinuous Arterial Spin Labeling with Optimized Tagging Efficiency - Shin, David D. (2012)
The adiabatic inversion of blood in pseudocontinuous arterial spin labeling (PCASL) is highly sensitive to off-resonance effects and gradient imperfections and this sensitivity can lead to tagging efficiency loss and unpredictable variations in cerebral blood flow (CBF) estimates. This efficiency loss is caused by a phase tracking error between the RF pulses and the flowing spins. This paper introduces a new method, referred to as Optimized PCASL (OptPCASL), that minimizes the phase tracking error by applying an additional compensation RF phase term and in-plane gradients to the PCASL pulse train. The optimal RF phase and gradient amplitudes are determined using a pre-scan procedure, which consists of a series of short scans interleaved with automated post-processing routines integrated to the scanner console. The pre-scan procedure is shown to minimize the phase tracking error in a robust and time efficient manner. As an example of its application, the use of OptPCASL for the improved detection of functional activation in the visual cortex is demonstrated and temporal SNR, image SNR, and baseline CBF measures are compared to those acquired from conventional PCASL.